Wonderland: The Image of Kāmarūpa in the Kālikāpurāṇa - Kooij, Karel R. Van (Religions, 2023)
In the Kālikāpurāṇa, the mountainous region of Kāmarūpa (roughly present Assam) is described as a ‘Wonderland’ where Hindu gods and goddesses are present in the form of mountains, wells, stones and rivers, and where people become immortal and reach a divine status. Death had no access there. The text, however, reports that after some time, all the sacred places in this region had been completely washed away by a flood of the Brahmaputra river. The gods disappeared. Wonderland became an ordinary land again, where people live and die. The way Kāmarūpa is described in this Purāṇa betrays the hand of a Brāhmin who accepted ‘correct’ Tantrism to some extent but preferred Vaiṣṇava standards. The relevant passages are translated anew and briefly discussed. The text itself is given the floor.